Prevalence screening for ovarian cancer in postmenopausal women by CA 125 measurement and ultrasonography. Issue 6884 (17th April 1993) - Jacobs, I; Davies, A P; Bridges, J; Stabile, I; Fay, T; Lower, A; Grudzinskas, J G; Oram, D
Abstract : OBJECTIVE–To assess the performance of the sequential combination of serum CA 125 measurement and ultrasonography in screening for ovarian cancer. DESIGN–The serum CA 125 concentration of each subject was determined and those with a concentration > or = 30 U/ml were recalled for abdominal ultrasonography. If ultrasonography gave abnormal results surgical investigation was arranged. Volunteers were followed up by annual postal questionnaire. SETTING–General practice, occupational health departments, ovarian cancer screening clinic. SUBJECTS–22, 000 women volunteers who were postmenopausal and aged over 45 years. MAIN OUTCOME MEASURES–Apparent sensitivity, specificity, positive predictive value, years of cancer detected. RESULTS–41 women had a positive screening result and were investigated surgically. 11 had ovarian cancer (true positive result) and 30 had other disorders or no abnormality (false positive result). Of the 21, 959 volunteers with a negative screening result, eight subsequently presented clinically with ovarian cancer (false negative result) and 21, 951 had not developed ovarian cancer during follow up (apparent true negative result). The screening protocol achieved a specificity of 99.9%, a positive predictive value of 26.8%, and an apparent sensitivity of 78.6% and 57.9% at one year and two year follow up respectively. The estimated number of years of cancer detected by the prevalence screen was 1.4 years. CONCLUSIONS–This screening protocol is highly specific for ovarian cancer and can detect a substantial proportion of cases at a preclinical stage. Further investigation is required to determine the effect of the screening protocol on the ratio of early to late stage disease detected and on mortality from ovarian cancer.